2019
DOI: 10.1155/2019/7486431
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcome in Infantile Autism with Folate Receptor Autoimmunity and Nutritional Derangements: A Self-Controlled Trial

Abstract: Background. In contrast to multiple rare monogenetic abnormalities, a common biomarker among children with infantile autism and their parents is the discovery of serum autoantibodies directed to the folate receptor alpha (FRα) localized at blood-brain and placental barriers, impairing physiologic folate transfer to the brain and fetus. Since outcome after behavioral intervention remains poor, a trial was designed to treat folate receptor alpha (FRα) autoimmunity combined with correction of deficient nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 61 publications
(65 reference statements)
3
45
1
Order By: Relevance
“…Overall, untreated patients, on average, did not demonstrate a change in CARS scores whereas children who underwent treatment demonstrated a decrease in CARS scores from severe to mild-to-moderate ASD. 56 Although this study is not specific for treatment with d,l -leucovorin, it does demonstrate that including d,l -leucovorin in a comprehensive treatment protocol can improve outcomes in core ASD symptoms. In a recent small (n = 19) French study, children with ASD were treated with 5 mg of d,l -leucovorin twice a day or placebo for 12 weeks under single-blind conditions.…”
Section: DL -Leucovorin Also Improves Core Symptoms Of Autimentioning
confidence: 70%
See 2 more Smart Citations
“…Overall, untreated patients, on average, did not demonstrate a change in CARS scores whereas children who underwent treatment demonstrated a decrease in CARS scores from severe to mild-to-moderate ASD. 56 Although this study is not specific for treatment with d,l -leucovorin, it does demonstrate that including d,l -leucovorin in a comprehensive treatment protocol can improve outcomes in core ASD symptoms. In a recent small (n = 19) French study, children with ASD were treated with 5 mg of d,l -leucovorin twice a day or placebo for 12 weeks under single-blind conditions.…”
Section: DL -Leucovorin Also Improves Core Symptoms Of Autimentioning
confidence: 70%
“… 55 In another study from Belgium, 2 groups of children with ASD demonstrated a 71.4% (n = 84) and 75.6% (n = 82) prevalence of at least one FRAA as compared to 3% of healthy children. 56 In a recent study from France, 58% of children with ASD were positive for at least one FRAA. 57 In a recent study from the New York City Metropolitan area, the prevalence of one or more FRAAs was 76% in children with ASD.…”
Section: Cerebral Folate Deficiency and Asdmentioning
confidence: 97%
See 1 more Smart Citation
“…Another possible explanation could be disturbed folate uptake from blood into cells. Recently, ASD onset has been related to FRα-autoantibodies, that seem to be prevalent in children with ASD and their relatives including their mothers [132][133][134][135][136]. Folate receptors alpha (FR )-autoantibodies prevent normal folate transport across the blood-brain barrier while normal content is observed in the blood [137] and may be a reason of folate insufficiency in cells with simultaneous high folate levels in blood.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal autoantibodies targeted against the Folate Receptor α (FRα) deserve to be mentioned in this section. Folate plays a key role in neural development during the embryo-fetal period and the early years of life [ 78 ]. Folate plays an essential role in cell-to-cell communication and in purine, methylation, and redox metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%